A new species of Osteospermum subgen. Tripteris (Asteraceae: Calenduleae) from the Namib Desert, Namibia - Swanepoel, Wessel; Cauwer, Vera De; Wyk, Abraham E. Van (Phytotaxa, 2021)
Osteospermum namibense, here described as a new species, is known only from the northern part of the Namib Desert in the Kaokoveld Centre of Endemism, northwestern Namibia. Within a broad generic concept for Osteospermum (tribe Calenduleae), the new species is a member of subgen. Tripteris. These dwarf shrubs grow on rocky outcrops under harsh desert conditions. Diagnostic characters for Osteospermum namibense include the perennial, woody habit, di- or trichotomous branching, succulent leaves arranged in rosettes, and capitula with 12–14 rays. A comparison of some of the more prominent morphological features to differentiate between O. namibense and its possible nearest relative, O. microcarpum (=Tripteris microcarpa), is provided. Based on IUCN Red List categories and criteria, a conservation assessment of Vulnerable (VU D1) is recommended for the new species.